As políticas públicas e os corpos subalternizados em tempos de pandemia: reflexões a partir da implementação do auxílio emergencial no Brasil - Dyego de Oliveira Arruda; Caroline Oliveira Santos (Ciências Sociais Unisinos)
This article aims to reflect on the public policy of emergency aid, revealing ways in which such strategy is capable (or not) of supporting subalternizated subjects in the context of the Covid-19 pandemic in Brazil. In summary, emergency aid represents a monthly amount, in cash, for people in a situation of socioeconomic vulnerability, with a family income less than ½ minimum wage per person. In general, it was possible to verify, throughout the reflections of this article, that emergency aid was important so that there were no more substantial falls in the average income levels of people, in the context of the pandemic. It is important to note that, even with emergency aid payments, the most precarious and vulnerable labor segments (such as self-employed workers and those without a formal contract) were those who suffered the most falls in their usual income levels, which suggests the existence of structural inequalities in the configuration of Brazilian society. In addition, it is important to highlight that certain profiles of subalternizated subjects had many difficulties in accessing the emergency aid, considering the criteria that were defined for the operationalization of the public policy in question. Therefore, we understand that the reflections of this article point to the need that the public policies (which, of course, includes the emergency aid strategy) to be more sensitive to the demands of subalternizated subjects, allowing them more possibilities to survive of the effects of Covid-19 pandemic.